Fungal chemical warfare: the role of aflatoxin and fumonisin in governing the interaction between the maize pathogens, Aspergillus flavus and Fusarium verticillioides - Timothy R. Satterlee; Jaci A. Hawkins; Trevor R. Mitchell; Qijian Wei; Jessica M. Lohmar; Anthony E. Glenn; Scott E. Gold (Frontiers in Cellular and Infection Microbiology)
The mycotoxigenic fungi, Aspergillus flavus and Fusarium verticillioides, commonly co-colonize maize in the field, yet their direct interactions at the chemical communication level have not been well characterized. Here, we examined if and how the two most infamous mycotoxins produced by these species, aflatoxin and fumonisin, respectively, govern interspecies growth and mycotoxin production. We showed that fumonisin producing strains of F. verticillioides suppressed the growth of A. flavus while non-producers did not. Additionally, while aflatoxin did not inhibit F. verticillioides growth, it did suppress fumonisin production. Fumonisin B1 concentration levels plummeted when challenged with a high dose of aflatoxin B1 or with an aflatoxin producing strain. With these findings, expression of the genetic regulators of secondary metabolism was investigated for both fungi. While no strong effect was seen on genes in the aflatoxin biosynthetic gene cluster when exposed to fumonisin B1, the fumonisin repressor FvZBD1, which is adjacent to the cluster, was induced with expression proportionate to concentration when F. verticillioides was challenged with aflatoxin B1. We also assessed the expression of the global regulators of fungal secondary metabolism, veA and laeA, and found that their expression is altered in both A. flavus and F. verticillioides when exposed to their competitor’s mycotoxin. This work gives insight into the ecological roles of mycotoxins and why these fungi may produce them as weapons in the interspecies battle for resource acquisition.